Fostering incremental and radical innovation through performance-based contracting in buyer-supplier relationships. Issue 11 (7th November 2016) - Sumo, Regien; van der Valk, Wendy; van Weele, Arjan; Bode, Christoph
Abstract : Purpose: While anecdotal evidence suggests that performance-based contracts (PBCs) may foster innovation in buyer-supplier relationships, the understanding of the underlying mechanisms is limited to date. The purpose of this paper is to draw on transaction cost economics and agency theory to develop a theoretical model that explains how PBCs may lead to innovation. Design/methodology/approach: Using data on 106 inter-organizational relationships from the Dutch maintenance industry, the authors investigate how the two main features of PBCs – low-term specificity and performance-based rewards – affect incremental and radical innovation. Findings: The authors find that term specificity has an inverse- U -shaped effect on incremental innovation and a non-significant negative effect on radical innovation. Furthermore, pay-for-performance has a stronger positive effect on radical innovation than on incremental innovation. The findings suggest that in pursuit of incremental innovation, organizations should draft contracts with low, but not too low, term specificity and incorporate performance-based rewards. Radical innovation may be achieved by rewarding suppliers for their performance only. Originality/value: The findings suggest that in pursuit of incremental innovation, organizations should draft contracts with low, but not too low, term specificity and incorporate performance-based rewards. Radical innovation requires rewarding suppliers for their performance only.